Application of Kotter's 8-steps model to reduce maternal mortality due to third delay in sub-Saharan Africa - Mpumelelo Sibanda; Enos Moyo; Tafadzwa Dzinamarira; Grant Murewanhema (Elsevier, 2024)
Maternal mortality remains a significant public health challenge globally, with most deaths occurring in lower-to-middle-income countries. Sub-Saharan Africa (SSA) accounted for 70% of global maternal deaths in 2020. The three-delays model is widely used to account for maternal deaths, with the third delay, which is attributed to delays in receiving intervention in healthcare institutions, being the most common cause. The third delay is attributed to several factors. Implementation of the interventions that can be used to address these factors can make use of Kotter's 8-step change model. Although there is limited evidence on the use of this model to reduce maternal mortality, it has been used in several industries with great success. In this article, we discuss the application of Kotter's model in addressing the third delay in SSA, as well as the challenges and recommendations in the application of the model. The use of the model in trying to reduce the third delay as a cause of maternal mortality may lead to some challenges. Some of the challenges include its paucity of information on how to sustain change, its numerous steps which are laborious and time-consuming, and its lack of usefulness when change requires a bottom-up approach. However, with some adjustments to the model, we believe that SSA can successfully use the model to reduce third delays as a cause of maternal mortality in the region.